Modulating proton diffusion and conductivity in metal–organic frameworks by incorporation of accessible free carboxylic acid groups. Issue 5 (29th November 2018) - Rought, Peter; Marsh, Christopher; Pili, Simona; Silverwood, Ian P.; Sakai, Victoria García; Li, Ming; Brown, Martyn S.; Argent, Stephen P.; Vitorica-Yrezabal, Inigo; Whitehead, George; Warren, Mark R.; Yang, Sihai; et al.
Abstract : The proton conductivity of barium-based MOFs MFM-510 to MFM-512 are analysed in relation to the absence and presence of free –COOH groups in the pores. Abstract : Three multi-carboxylic acid functionalised ligands have been designed, synthesised and utilised to prepare the new barium-based MOFs, MFM-510, -511, and -512, which show excellent stability to water-vapour. MFM-510 and MFM-511 show moderate proton conductivities (2.1 × 10 −5 and 5.1 × 10 −5 S cm −1, respectively) at 99% RH and 298 K, attributed to the lack of free protons or hindered proton diffusion within the framework structures. In contrast, MFM-512, which incorporates a pendant carboxylic acid group directed into the pore of the framework, shows a two orders of magnitude enhancement in proton conductivity (2.9 × 10 −3 S cm −1 ). Quasi-elastic neutron scattering (QENS) suggests that the proton dynamics of MFM-512 are mediated by "free diffusion inside a sphere" confirming that incorporation of free carboxylic acid groups within the pores of MOFs is an efficient albeit synthetically challenging strategy to improve proton conductivity.